Beyond Festive Peaks: An Empirical Study of Consumer Behaviour and Strategic Marketing Recommendation for Indonesia’s Cordial Syrup Brand - Fajrinia, Lestri (Journal Research of Social Science, Economics, and Management, 2026)
The cordial syrup category has long been established in the Indonesian market with high dependency on Ramadhan and Idul Fitri periods. Despite consistently high seasonal marketing investment and strong brand awareness, the category has reached consumption stagnation, indicating that traditional promotion-driven strategies are no longer able to generate sustainable growth. This study aims to re-examine cordial syrup consumer behavior and explore untapped insights as opportunities for business growth through consumer-driven activation and innovation. The research employed a qualitative approach through in-depth interviews with six cordial syrup consumers in Jakarta and Medan. The collected data were analyzed using thematic analysis and synthesized by integrating findings with literature and business context. The results identify eight major themes influencing cordial syrup consumption: emotional, personal, social, cultural, product and packaging, price, place, and promotion and communication factors. These factors interact dynamically and shape consumer purchasing decisions. The findings demonstrate that consumer expectations have evolved faster than the industry's current marketing strategy. The emergence of healthy lifestyles, greater convenience needs, creative inspiration, and year-round relevance represent blue ocean areas that can be leveraged for a more progressive marketing approach. Every product and packaging innovation should be supported by new value creation that enables consumers to experience better emotional and social fulfillment. From a strategic marketing perspective, this study concludes that sustainable growth in the cordial syrup category requires consumption expansion, strengthening the brand's emotional and cultural relevance, and repositioning the brand as an everyday family beverage solution.